PARTICIPATORY ACTIONS, PARTICIPATORY ART, AND RURAL LIFE IN THE POST-INDUSTRIAL CITY OF ASPROPYRGOS - Bouriti, Emilia (Design/Arts/Culture, 2023)
The portfolio is a presentation of research and artistic practice used by the artist based on the role of participatory art in her collaboration with the rural Arvanitic community of the post-industrial city of Aspropyrgos. A Greek city located 18 kilometres west of Athens. An example of artistic practice is presented in the international interdisciplinary program "Amoli - Art and Culture: a collective project in the rural, post-industrial, multicultural community of Aspropyrgos" (the word 'Amoli' means to the farmers of Aspropyrgos the water through that irrigates the agricultural crops). The program is implemented in Aspropyrgos, a historically rural town, which went through a violent industrial development and is now going through its post-industrial phase, while the intense migration flow shaped the city's multicultural physiognomy. The portfolio presents the participatory actions of a diverse audience involved in the creation of the artistic work consisting of narratives, participation in agricultural work, participatory meals, walking routes, as well as holistic educational actions since the participants, despite belonging to different social groups, learn and collectively gets trained in the above mentioned actions. The above provides food for the creation of interdisciplinary visual works that are presented in rural areas, turning them into modern art spaces and bringing out questions that concern the international community, indicatively such as the value of arable land and food, the link of modern man with nature, the preservation of the cultural heritage of rural communities, the future of spoken languages. The Amoli international program through the practice of participatory art creates projects that respond to the above needs.